Tunable excitonic transitions in strained GaAs ultra-thin quantum disk. (February 2017) - El-Yadri, M.; Aghoutane, N.; Feddi, E.; Dujardin, F.
Abstract: Simultaneous influences of hydrostatic pressure and temperature combined to the size effect on the behaviour of the exciton in 2D A l A s / G a A s / A l A s ultra thin quantum disk are investigated. Our approach is performed in the framework of effective mass theory and adiabatic approximation by using a variational method with a robust trial wave function and by taking into account the dependence of the size, the dielectric constant and the effective masses on the pressure and temperature. Variations of the excitonic binding energy, photoluminescence energy and oscillator strength are determined according to hydrostatic pressure and temperature for different confinement regimes. The results of our numerical calculations show that the applied pressure favours the electron-hole attraction while the temperature tends to decrease the exciton binding energy. Another interesting result is the possibility of transforming a thin quantum disk into a large-gap material by strain effect. The opposing effects caused by temperature and pressure reveal a big practical interest and offer an alternative way to the tuning of the excitonic transition in optoelectronic devices. Highlights: Tunable excitonic transition under pressure and temperature. Pressure and temperature dependence of the oscillator strength. Competitive effects of quantum dots size, temperature and pressure on the exciton binding energy. Enlargement of optical band gap induced by strain.